2007
DOI: 10.1111/j.1600-0846.2007.00264.x
|View full text |Cite
|
Sign up to set email alerts
|

Study of skin–fabric interactions of relevance to decubitus: friction and contact‐pressure measurements

Abstract: TFA measurements allow the objective and reliable study of the tribology of the skin-textile biointerface and will be used to develop medical textiles with improved performance and greater efficacy for decubitus prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
87
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(91 citation statements)
references
References 54 publications
2
87
0
Order By: Relevance
“…Considering the respective normal forces during the rubbing process (approx. 15 N), the average apparent contact pressures were 3.4G0.5 kPa, which is close to the maximum interface pressures observed for supine persons (Defloor 2000;Gerhardt et al 2008).…”
Section: Contact Area Measurementssupporting
confidence: 77%
See 1 more Smart Citation
“…Considering the respective normal forces during the rubbing process (approx. 15 N), the average apparent contact pressures were 3.4G0.5 kPa, which is close to the maximum interface pressures observed for supine persons (Defloor 2000;Gerhardt et al 2008).…”
Section: Contact Area Measurementssupporting
confidence: 77%
“…In the present study, the average variation coefficient of the measured COFs was 5.1%. This value was higher than the variation coefficients found in experiments, in which normal loads and sliding motions were machine controlled (Sivamani et al 2003b,c;Gerhardt et al 2008), but indicated a sufficient sensitivity and reliability of the 'direct touch' in vivo friction measurement method.…”
Section: Study Limitationsmentioning
confidence: 59%
“…26 This could also contribute in the prevention of the decubitus ulcers, as the creation of ulcers depends on the friction between skin and the bedsheet. 63 …”
Section: Discussionmentioning
confidence: 99%
“…The average normal load of all subjects was (14.6 AE 1.3) N, which reflects individual normal load variations ranging from 11 to 19 N. The mean dynamic skin friction coefficient (COF) obtained from at least 15 full friction cycles was calculated by the ratio of friction force and normal force, and used for further statistical analyses. Before the friction experiments, the apparent contact area between the skin and the force plate was determined using a pressure-sensitive film (19 (31).…”
Section: Study Participantsmentioning
confidence: 99%